Mixed germ cell tumour of testis: a case report with review of literature - Kumar, S. V.; Naik, M. Bhagavan; Harshvardan, M. S. R.; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Testicular tumours are rare neoplasm. Mixed germ cell tumour is the most common histological variant. Essentially, any admixture of the germ cell tumours as seen in pure form may be seen, one of the most common admixtures being embryonal carcinoma and teratoma. Unfortunately many of these patients present late usually with some complications. We present a rare case of mixed germ cell tumour with predominant embryonal carcinoma and yolk sac tumour in adolescent patient with multiple metastatic foci at the time of presentation.